Blood levels of serotonin and tryptophan and their relationship with mood changes during pregnancy and postpartum period - Helal Uddin, A.B.M.; Khan, Umeed Ali; Saeed, Mohammad; Zainuddin, Ahmad Murad (University of Peshawar, 2012)
The mood changes during pregnancy and postpartum period was recorded in 104 women belonging to various ethnic groups. The study was conducted in a hospital after institutional approval for the consented females. The information were recorded by interview of the study subject using a validated questionnaire. The analysis of questionnaire showed that 23.08% (24) women were clinically depressed during pregnancy and, 22.61 % (23) women after childbirth. However these 23 women included 8 women who were already depressed prenatally. On exclusion of these 8 cases, the postnatal depression was observed in 14.4%. Thirty (29.76%) women experienced a brief period of "pathological" happiness (joy of motherhood) after childbirth. The levels of serotonin and tryptophan were determined in two groups of subjects identified as who experienced depression during pregnancy and after childbirth. The blood samples (during pregnancy and postpartum period) were analysed for serotonin and tryptophan quantification using a validated HPLC method. The tryptophan level in prenatal depression and postpartum depression was found to be 12.7 ±2.5 and 11.9 ±2.4 ng/ml, respectively and that of the serotonin was 7.4 ± 1.8 and 7.7 ±1.7 ng/ml, respectively in the above groups. It was concluded that the blood level of tryptophan and serotonin can guide us in the prevention and control of depression.